Seed germination and seedling growth of Chiococca javanica (Rubiaceae) in relation to fruit maturation and media growth - PURWANTORO, R. SUBEKTI (Nusantara Bioscience, 2017)
Purwantoro RS. 2017. Seed germination and seedling growth of Chiococca javanica (Rubiaceae) in relation to fruit maturation and media growth. Nusantara Bioscience 9: 111-119. Chiococca javanica is a plant having ornamental potential. The seeds extracted from the fruits were classified according to maturity stage: Unripe - yellow; ripe - reddish; and over ripe - dark-red and seed germination were done in two germination media: sand and rice husk. The statistical approach was a randomized complete block design with three replications. Analysis of variance indicated that the seeds of C. javanica from the ripe and over ripe fruit had higher significances (P
Keywords: Chiococca javanica; fruit maturation; seed germinations; seedling growth